Characterization of Conserved Coconut Germplasm in Sri Lanka with Morphological Descriptors - Suriya A. C. N. Perera; G. K. Ekanayake; R. B. Attanayake (International Coconut Community, 2009)
Characterization of conserved germplasm is of primary importance for genetic resources to be effectively used and for formulating further conservation strategies. The aim of the research reported in the current paper is to characterize 26 coconut germplasm accessions conserved ex-situ at Pottukulama field gene bank in Sri Lanka using morphological descriptors. A total of 17 stem, leaf and inflorescence traits listed for coconut by Bioversity International were scored in 30 randomly selected palms in each accession. Twenty six germplasm accessions evaluated included 5 dwarf accessions out of which 2 were of exotic origin and 21 Sri Lankan tall coconut accessions. Statistical analytical methods; principal component analysis, cluster analysis and correlation calculation were performed in Minitab version 11 while General linear models procedure and mean separation techniques were performed in SAS version 8. The first 3 principal components cumulatively explained 88.2% of the variation present among accessions. Stem, leaf characters and the length of central axis along with overlapping of male and female phases were identified as the main morphological traits distinguishing the evaluated germplasm. Talls and the dwarf groups separated clearly while the variation within the tall accessions was found to be very narrow. The exotic dwarf Brazilian green dwarf showed the highest distance with the tall accessions while the accession Brown dwarf was the furthest from the talls out of the local dwarfs indicating their potential for hybridizing with talls for maximum heterosis. Results further indicate that future germplasm collection should be based more on biased selection for distinct morphological features rather than random selections within tall populations in Sri Lanka.